If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -32 = 2x Reorder the terms: -32 + 6x = 2x Solving -32 + 6x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -32 + 6x + -2x = 2x + -2x Combine like terms: 6x + -2x = 4x -32 + 4x = 2x + -2x Combine like terms: 2x + -2x = 0 -32 + 4x = 0 Add '32' to each side of the equation. -32 + 32 + 4x = 0 + 32 Combine like terms: -32 + 32 = 0 0 + 4x = 0 + 32 4x = 0 + 32 Combine like terms: 0 + 32 = 32 4x = 32 Divide each side by '4'. x = 8 Simplifying x = 8
| -1=3-4 | | 51+y/3=63 | | y=15/x | | 0=4-4 | | 9/8*2/3 | | X^2+0.0007X-0.007=0 | | 41/2-1/3 | | 2*-8=12 | | 3x^2/3+8x^1/3+5=0 | | 3/2*7/9 | | x^3-16x^2+8x=0 | | -6=3*-2 | | -3m-7=34 | | -6(8r-16)=-72 | | 7/4*6/5 | | a+4a=144 | | 5=1-2 | | -y=-2-6x | | 4-2/7 | | 32u+14u^2-u^3=0 | | 2/5*20 | | 4-9=x+3 | | y/3+2=4/5 | | y(3y^2)=648 | | 4/7*49 | | 32=4k+8 | | 11x+13=12x+6 | | 3x(x)+9=84 | | 12z+29= | | -2=-6r+4r | | 4/9*27 | | 5+7y=47 |